Biological roles of sulfur dioxide and sulfite in the regulation of mitochondrial viscosity. Issue 61 (8th July 2022) - Zhang, Weijie; Lv, Yunxia; Song, Hongjun; Huo, Fangjun; Zhang, Yongbin; Yin, Caixia
Abstract : A viscosity-sensitive NIR fluorescent probe has been developed for the visualization of the cross-talk behavior between mitochondrial viscosity and SO2 /SO3 2− . Abstract : Herein, a NIR fluorescent probe has been developed for visualization of the roles of SO2 /SO3 2− in mitochondrial viscosity. The results showed that SO3 2− would increase mitochondrial viscosity and decrease mitochondrial membrane potential (MMP). However, increasing SO2 stimulation decreased mitochondrial viscosity and caused inconspicuous MMP changes.